First live birth after uterus transplantation in the United States. Issue 5 (12th April 2018) - Testa, G.; McKenna, G. J.; Gunby, R. T.; Anthony, T.; Koon, E. C.; Warren, A. M.; Putman, J. M.; Zhang, L.; dePrisco, G.; Mitchell, J. M.; Wallis, K.; Klintmalm, G. B.; et al.
Abstract : Uterus transplantation has proven to be a successful treatment for women with absolute uterine infertility, caused either by the absence of a uterus or the presence of a nonfunctioning uterus. We report the first birth of a healthy child following uterus transplantation in the United States, from a recipient of a uterus allograft procured from an altruistic living donor. Two major modifications from the previously reported live births characterized this uterus transplant. First, the transplanted uterus relied upon and sustained the pregnancy while having only the utero‐ovarian vein as venous outflow. The implication is a significantly simplified living donor surgery that paves the way for minimally invasive laparoscopic or robot‐assisted techniques for the donor hysterectomy. Second, the time from transplantation to embryo transfer was significantly shortened from prior protocols, allowing for an overall shorter exposure to immunosuppression by the recipient and lowering the risk for potential adverse effects from these medications. Abstract : Testa et al report the first live birth in the United States after uterus transplantation, with two major modifications from the previously reported live births: The transplanted uterus relied upon and sustained the pregnancy while having only the utero‐ovarian vein as venous outflow, and the time from transplantation to embryo transfer was significantly shortened from prior protocols.